The Effect of Financial Literacy and Credit Procedures on Credit Taking Decisions - Sady, Muhammad; Rasyid, Abdul; Pasolo, Fahrudin (Advances in Economics & Financial Studies, 2024)
Purpose: This study aims to determine the effect of Financial Literacy on Credit Decision Making. To assess the effect of Credit Procedures on Credit Taking Decisions. Moreover, to determine the impact of Financial Literacy and Credit Procedures on Credit Decision Making. Research Design and Methodology: The population in this study were debtors of Bank BRI Jayapura City Unit Office who applied for credit in 2021-2022, totaling 1,714 debtors. The sampling technique used in this study is proportional random sampling. Data sources use primary data and secondary data. The statistical analysis method used in this research is Multiple Linear Regression Analysis based on the T Statistical Test technique, F Statistical Test, and the Coefficient of Determination with the help of SPSS version 29 software. Findings and Discussion: The results showed that Financial Literacy has a positive and significant effect on Credit decision-making, and credit procedures have a positive and significant effect on credit decisions. Financial Literacy and Credit Procedures simultaneously affect the decision to take credit at BRI Bank Jayapura City Unit. Implications: This research is expected to significantly influence future studies in economics, particularly financial management. The results are also likely to serve as a reference and comparison material for further research related to credit decision-making.